(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Laryngeal cancer accounts for 2% of all diagnosed cancers, with approximately 151,000 new cases occurring annually. The aim of this research was to study the laboratory parameters of fibrinogen by investigating the difference in fibrinogen values in patients before and after surgery, and then comparing these values with a control group. The study included all patients diagnosed with laryngeal cancer who visited the Department of Otolaryngology and Head and Neck Surgery at Tishreen University Hospital in Latakia, and who underwent surgery for this tumor, after obtaining informed consent. A prospective study was conducted, and the number of patients was 30. A special research form was prepared for the patients. The results of the study showed that fibrinogen levels in patients with laryngeal cancer increase after surgery compared to their levels before surgery. There was a statistically significant difference in fibrinogen levels in patients with laryngeal cancer before and after surgery compared to the control group. The study recommends further studies to understand the mechanisms of change in fibrinogen levels after surgery. These studies may include: Analyzing the interactions between surgery, inflammation, and coagulation. Evaluating the effect of different factors on fibrinogen levels, such as cancer stage, type of treatment, and the presence of surgical complications on fibrinogen levels and patient outcomes.